Non-Pharmacological Treatments of Neuropsychiatric Symptoms in Mild Cognitive Impairment - Thurin, Kristina; Daffner, Kirk; Gale, Seth; Donovan, Nancy J.; Urizar, Juan Carlos (Seminars in Neurology, 2022)
Mild cognitive impairment (MCI) is a syndrome defined by objective cognitive deficits that do not impact functional independence. Individuals with MCI develop dementia at an annual rate of 10 to 15%. Neuropsychiatric symptoms (NPS) are common non-cognitive features of neurocognitive disorders and have a major impact on the wellbeing and quality of life of affected individuals and their families. Non-pharmacological interventions for NPS are considered the first-line treatment because of the limited efficacy and side-effect potential of current pharmacological agents. This article summarizes the literature on non-pharmacological treatments for NPS in MCI. The limited number of studies specific to individuals with MCI and its various etiologies, as well as the overall heterogeneity of research design and methodologies, make the evidence base inconclusive. Nevertheless, some studies support psychosocial interventions aimed at individuals with MCI and their caregivers.
Keywords: mild cognitive impairment; neuropsychiatric symptoms; non-pharmacologic interventions; neuropsychiatry; behavioral neurology